2023
DOI: 10.1111/avsc.12722
|View full text |Cite
|
Sign up to set email alerts
|

Rangeland resilience to droughts: Changes across an intensification gradient

Abstract: The intensification of livestock systems generates structural and functional changes in native grassland, which alter their capacity to respond to disturbances. Our objective was to evaluate the resilience to an extraordinary consecutive droughts event, across an intensification gradient of pastoral systems. Our prediction is that sites with more intensive management (less diverse) will have lower resilience (as resistance and/or recovery) to drought. LocationSouth-central region of Uruguay. MethodsWe evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 108 publications
(204 reference statements)
0
2
0
Order By: Relevance
“…However, by maintaining adequate vegetation cover and leaf area index, water loss through evapotranspiration is minimized, leading to increased water availability for ecosystem services, other purposes and the restoration of degraded ecosystems (Irob, Blaum, Weiss-Aparicio, et al, 2023;Tommasino et al, 2023).…”
Section: Climate Change-related Uncertainty In Vegetation In Grazing ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, by maintaining adequate vegetation cover and leaf area index, water loss through evapotranspiration is minimized, leading to increased water availability for ecosystem services, other purposes and the restoration of degraded ecosystems (Irob, Blaum, Weiss-Aparicio, et al, 2023;Tommasino et al, 2023).…”
Section: Climate Change-related Uncertainty In Vegetation In Grazing ...mentioning
confidence: 99%
“…However, the extent of change required can vary based on the specific system and location, necessitating either incremental adjustments or more transformative step changes in management strategies. For instance, rangeland managers could consider measures such as preventing shrub encroachment, actively maintaining biodiversity, optimizing grazing practices and fostering resilient vegetation cover (Higgins et al, 2007;Tommasino et al, 2023;Wangai et al, 2016). These approaches should be evaluated within the context of their economic viability and potential benefits for sustaining ecosystem health and services.…”
Section: Introductionmentioning
confidence: 99%
“…Such drought periods have a significant impact on forage production and, hence, on livestock productivity, including a drastic reduction in reproductive performance that causes lag effects on Net Secondary Productivity (Gutierrez et al 2020). It has been recently reported that areas with a greater diversity of perennial forage resources (native grasslands, intersown grasslands or pasture based on exotic pastures) are more resilient to droughts events (Tommasino et al 2023).…”
Section: Introductionmentioning
confidence: 99%